2010
DOI: 10.1074/jbc.m109.031476
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cell Lymphotropic Virus 1 Manipulates Interferon Regulatory Signals by Controlling the TAK1-IRF3 and IRF4 Pathways

Abstract: We previously reported that human T cell lymphotropic virus 1 (HTLV-1) Tax oncoprotein constitutively activates transforming growth factor-␤-activated kinase 1 (TAK1). Here, we established Tax (5) and cytosolic viral RNA sensors, such as RIG-I (6) and MDA5 (7). In contrast, IRF4, another member of the IRF family that is preferentially expressed in lymphoid cells, was first identified as a transcription factor that negatively regulates the activity of IFN-regulated genes (8) and TLR signaling (9). Human T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 31 publications
1
39
3
Order By: Relevance
“…Other IRFs that are important players in the production of type I IFNs, including at least IRF1, -3, and -7, IRF7, -4, and -2, three IRFs with oncogenic properties, are associated with EBV latency and may contribute to EBV oncogenesis. Overwhelming evidence also shows that IRF4 is overexpressed in HTLV1-infected cells and associated tumors (51,58,61,74), suggesting that IRF4 may play a key role in HTLV1 tumorigenesis. Regulation of IRF4 expression in the context of HTLV1 infection is complicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other IRFs that are important players in the production of type I IFNs, including at least IRF1, -3, and -7, IRF7, -4, and -2, three IRFs with oncogenic properties, are associated with EBV latency and may contribute to EBV oncogenesis. Overwhelming evidence also shows that IRF4 is overexpressed in HTLV1-infected cells and associated tumors (51,58,61,74), suggesting that IRF4 may play a key role in HTLV1 tumorigenesis. Regulation of IRF4 expression in the context of HTLV1 infection is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Among IRFs, IRF2, -4, and -7 have oncogenic potentials (41). IRF4 is overexpressed in EBVtransformed cells (73) and in multiple myeloma (24,57), as well as in human T-cell leukemia virus type 1 (HTLV1)-infected cell lines and associated adult T-cell lymphoma/leukemia (ATLL) (51,58,61,74). IRF7 has been shown to be associated with EBV latency and is overexpressed in a subset of EBV-positive and -negative lymphomas/leukemias (41).…”
mentioning
confidence: 99%
“…Likewise, IRF4 was found to be constitutively expressed in ATL as opposed to nonlymphocytic HTLV-1 infection (48). A number of studies have linked activating mutations and high levels of expression of IRF4 with HTLV-1 infection, with IRF4 expression resulting in reduced expression levels of genes previously shown to be dysregulated in ATL cases (48)(49)(50)(51)(52)(53). As proviral integration was found in the 5= ends of both of these genes, it is possible that integration may alter gene expression and thus may have contributed to transformation or ATL.…”
Section: Discussionmentioning
confidence: 99%
“…232 Both phenylephrine-or endothelin-1-stimulated cardiomyocyte enlargement in vitro and AB-induced cardiac hypertrophy in vivo have identified the bona fide suppressive function of A20 on hypertrophic responses based on its negative regulation of NF-κB and the transforming growth factor-beta (TGF-β)-activated kinase 1 (TAK1)-dependent JNK/p38 signaling cascade. [233][234][235] Suzuki et al 236 reported that A20 overexpression markedly induced the activation of IRF3 in a TAK1-dependent manner that was negatively regulated by IRF4 in response to stimulation with human T-cell lymphotropic virus. These studies suggested that A20/TAK1/IRFs might form a crucial signaling cascade to regulate cardiac remodeling; however, this hypothesis must be further confirmed.…”
Section: Upstream Irf Signaling In Cardiac Remodelingmentioning
confidence: 99%